Shrimp Price and Quality Changes in the Asia Pacific: Implications for the Philippines - Nerissa D. Salayo (Philippine Institute for Development Studies (PIDS), 2000)
This paper represents an attempt to begin developing the use of a set of hedonic price indexes (HPIs) that account for quality changes in the shrimp industry in the Asia Pacific. Some implications and opportunities for the Philippines are presented to provide a starting point for future research directions. In particular, this paper aims to investigate the changes in price-quality relationships through time. Such changes are determined by the three main factors, such as changes in product quality, changes in the general price level (inflation) and changes in quality-constant relative product price.
Keywords: 330; shrimp industry; Fischereiprodukt; Meerestiere; Produktqualität; Asiatisch-pazifischer Raum